Clinico-Demographic Characteristics and Different Diagnostic Findings of Epilepsy Patients in a Specialized Hospital Outside Dhaka in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Epilepsy is a common neurological conditions. It is a global problem affecting all ages, social classes, groups and countries. Objective: The purpose of the present study was to see the clinico-demographic characteristics and different diagnostic findings of epilepsy patients. Methodology: This cross sectional study was carried out in the Department of Neurology at Shaheed Sheikh Abu Naser Specialized Hospital, Khulna, Bangladesh from November, 2012 to February, 2014. The patients were recruited from the epilepsy clinic. Clinical diagnosis of epilepsy was made by meticulous history and relevant clinical examination by the investigator. Routinely electroencephalography (EEG) was advised and interpreted by the investigator and MRI was advised in appropriate cases.Results: A total number of 115 epilepsy patients were recruited of which 77(67.0%) were male and 38(33.0%) were female. Most [95(83.7%)] of the patients were young (age group 0 to 29 years) and had partial seizures 89 (77.39%). Among these partial seizures most had complex partial seizure (CPS) [82(71.3%)] of which 53 (46.1%) had complex partial seizures-Temporal (CPS-T) and 29 (25.2%) had complex partialseizures-extra-temporal (CPS-ET) origin. EEG could be done in 76 patients. Among them 37(48.7%) had different types of abnormalities. MRI could be done in 52 patients and were found to be abnormal in 32(61.5%) patients.Conclusion: This study revealed that localization related epilepsy (LRE) is more common but the etiology remains undetermined in many cases. Therefore, more effort and investigation facilities are needed to identify the etiology. The high number of extra temporal lobe epilepsy (Ex-TLE) needs further evaluation in bigger sample.Journal of National Institute of Neurosciences Bangladesh, 2016;2(1): 3-9